An Investigation of Open Innovation Paradigm Using Value Chain Framework: A Case of Indonesian Milk Cooperative - Hisyam Hisyam; Rifi Wijayanti Dual Arifin; Yuliani Dwi Lestari; Yoshiyuki Matsuura (International Journal of Supply Chain Management, 2019)
Milk cooperative has struggled in facing numerous challenges as the complexity of its organization increase constantly, yet the cooperative is lack of capability to tackle the impediments. Under that circumstances, a milk cooperative which prone to fail in supplying a good quality of raw milk need to collaborate in order to keep the operational at a bearable cost. Since such strategy objective demand high technological equipment for its cold chain, milk cooperative has no choice but to be open and collaborate with academicians, business partners, communities, and government. Through a case study, this paper shows the practicality implementation of open innovation in one of the leading milk cooperatives in Indonesia. In order to provide a better understanding, the use of Porters value chain in mapping the milk chain and its innovation partners are presented. The mapping also being transformed into the rich picture to elevate the clarity regarding roles of each stakeholder along the value chain in boosting milk cooperative value proposition. The result shows the open innovation concept is applicable at any stage of the milk chain and the practice has proven in increasing cooperative innovativeness.